Per un ricordo dell’amicizia friburghese tra Jean de Menasce e Gianfranco Contini - Paolini, Michele (Verbum – Analecta Neolatina, 2018)
This work aims to outline a comprehensive account of the intellectual friendship that developed in Fribourg, Switzerland in 1938, between the Dominican Jean de Menasce, a converted Jew, a Hungarian baron, the first to translate T. S. Eliot into French, and the young Gianfranco Contini, already a well-known Italian philologist and literary critic. We emphasize the strategic character of this friendship, inspired by an esprit européen that had deep speculative and epistemological roots, and nourished by the thought of Jacques Maritain, who exercised specific influences on the cultural environment of the University of Fribourg at that time.